2015
DOI: 10.3945/jn.114.200931
|View full text |Cite
|
Sign up to set email alerts
|

The Green Algal Carotenoid Siphonaxanthin Inhibits Adipogenesis in 3T3-L1 Preadipocytes and the Accumulation of Lipids in White Adipose Tissue of KK-Ay Mice

Abstract: These results provide evidence that siphonaxanthin may effectively regulate adipogenesis in 3T3-L1 cells and diabetic KK-Ay mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 44 publications
1
37
2
Order By: Relevance
“…Although these green algae have been eaten for a long time, especially in Japan, studies on intestinal absorption of siphonaxanthin are limited. In a recent study, we showed that when mice were subjected to a daily intake of siphonaxanthin (1.3 mg/mouse dissolved in 100 μL triolein) over a period of 6 weeks, it resulted in its accumulation in mesenteric white adipose tissues (389.8 ± 30.2 ng/g tissue) (Li et al, ). In addition, we found that, in green algal powder‐fed mice, whose daily siphonaxanthin intake was around 31.1 μg over a period of 78 days, the carotenoid accumulated in mesenteric white adipose tissues (5.57 ± 1.80 ng/g tissue) (Li et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these green algae have been eaten for a long time, especially in Japan, studies on intestinal absorption of siphonaxanthin are limited. In a recent study, we showed that when mice were subjected to a daily intake of siphonaxanthin (1.3 mg/mouse dissolved in 100 μL triolein) over a period of 6 weeks, it resulted in its accumulation in mesenteric white adipose tissues (389.8 ± 30.2 ng/g tissue) (Li et al, ). In addition, we found that, in green algal powder‐fed mice, whose daily siphonaxanthin intake was around 31.1 μg over a period of 78 days, the carotenoid accumulated in mesenteric white adipose tissues (5.57 ± 1.80 ng/g tissue) (Li et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that siphonaxanthin was absorbed from the diet. Moreover, we reported various activities of siphonaxanthin that could be potential health benefits, such as apoptosis‐inducing effect on cancer cells (Ganesan et al, ), anti‐obesity effect (Li et al, ), inhibitory effect on hepatocyte lipogenesis (Zheng et al, ), and anti‐inflammatory effect (Manabe et al, , , b). To explore these biological activities, information on the intestinal absorption mechanism of siphonaxanthin is mandatory.…”
Section: Introductionmentioning
confidence: 99%
“…Following this study, it is plausible to speculate that SPX may have some unique effect targeting pathological liver disorders such as NAFLD/NASH. Previously, we have reported that SPX inhibited mast cell degranulation and showed anti obesity activity in a diabetic and obese rodent model (Li et al, ; Manabe et al, ). These reports, in other aspects, together with this research indicate that SPX may be biologically multifunctional through exhibiting anti‐inflammation, anti obesity, and hepatoprotective effects.…”
Section: Discussionmentioning
confidence: 92%
“…) is a rare marine carotenoid abundant in green algae such as Codium fragile , Umbraulva japonica , and Caulerpa lentillifera (Sugawara, Ganesan, Li, Manabe, & Hirata, ). To date, antiangiogenesis, anti degranulation, and anti obesity effects of SPX have been reported but its effect on hepatic lipid metabolism remains unexplored (Ganesan et al, ; Li et al, ; Manabe, Hirata, & Sugawara, ). Siphonein (SPN; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Siphonaxanthin administration reduced the total weight of WAT, especially the mesenteric WAT in KK-Ay mice, and enhanced fatty acid oxidation in adipose tissue. 116 Okada et al 117 tested the suppressive effects of 13 naturally occurring carotenoids (lutein, violaxanthin, α-carotene, β-carotene 5,6-epoxide, canthaxanthin, citranaxanthin, rhodoxanthin, β-cryptoxanthin, antheraxanthin, lutein epoxide, neoxanthin, and capsorubin) on 3T3L1 adipocyte differentiation. They demonstrated that neoxanthin reduced intracellular lipid accumulation and the expression of C/ EBPα and PPARγ mRNAs without affecting the expression of C/EBPβ or C/EBPγ mRNAs.…”
mentioning
confidence: 99%